Quality improvement in rice (Oryza sativa) seed through mechanical seed processing - SINHA, J P; VISHWAKARMA, M K; ATWA, S S; SINHA, S N (The Indian Journal of Agricultural Sciences, 2014)
Quality seed improvement in rice (Oryza sativa L.)through a series of seed-processing machines was investigated during the rainy season 2000-2001. The processing machines proved an efficient tool in producing quality seeds. TheÂ  consistent and higher seed quality (germination 93% and physical purity 99.9%) could be achieved by efficient use of processing machines. The product and separate (reject) form individual machines were analysed to evaluate machine efficiency in separating the seed components as well as impurities from the harvested lot. The air-screen machines were found effective in remocintg dead seeds, whearease specific gravity separator removed abnormal seeds significantly. Gradual rice in seed quality was recorede with decrease in recovery in the processing line. Seeds significantly. Gradual rise in seed quality was recorded with decrease in recovery in the processing line. Seed loss in reject port was always associated with handling of seed lots by each machine. The total seed loss was observed only 1.30%. Specific gravity separator was found essential for the seed lot of medium-term storage (for 2 or more seasons) or for the buffer stocking. Matgenatical indices for cleaning efficiency, separation efficiency and process effiency were computed form the basic data to determine machine performance. X-ray imaging was unsed to evaluate instant seed quality and invisible damages in ht e well as rejects at each stages of processing line.